2022
DOI: 10.3389/fnut.2022.822557
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine, Coffee, Tea and Risk of Rheumatoid Arthritis: Systematic Review and Dose-Response Meta-analysis of Prospective Cohort Studies

Abstract: ObjectiveProspective cohort studies on coffee, tea and caffeine in relation to the risk of rheumatoid arthritis (RA) have shown conflicting results. The aim of this study was to conduct a dose–response meta-analysis of cohort studies on the association between dietary caffeine, different types of coffee and tea consumption and the risk of RA.MethodsPubMed/Medline, Scopus and EMBASE were searched up to July 2021 to identify relevant studies that had considered different types of coffee (caffeinated or decaffein… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…Previous prospective studies have shown that coffee intake was not associated with RA risk ( 10 – 12 ). However, Mikuls et al found that decaffeinated coffee intake was independently positively correlated with RA risk, while the caffeinated coffee intake was not associated with RA rise ( 13 ) and similar results were obtained by a meta-analysis by Asoudeh et al ( 14 ). Overall, their results were not consistent.…”
Section: Introductionsupporting
confidence: 63%
“…Previous prospective studies have shown that coffee intake was not associated with RA risk ( 10 – 12 ). However, Mikuls et al found that decaffeinated coffee intake was independently positively correlated with RA risk, while the caffeinated coffee intake was not associated with RA rise ( 13 ) and similar results were obtained by a meta-analysis by Asoudeh et al ( 14 ). Overall, their results were not consistent.…”
Section: Introductionsupporting
confidence: 63%
“…It is commonly employed in both medical and recreational contexts to alleviate fatigue and sleepiness, as well as to enhance performance in a cost-effective manner, hence reducing the overall likelihood of developing cancer. Furthermore, it is more effectively acknowledged as a non-enzymatic antioxidant [ [66] , [67] , [68] ].…”
Section: Resultsmentioning
confidence: 99%
“…Az NHS II. vizsgálat negatív összefüggést mutatott ki a kávéfogyasztás és a C-reaktív protein (CRP), az interleukin-6, a tumornekrózisfaktoralfa (TNFα) és más gyulladásos markerek között [8].…”
Section: éLelmi Anyagok éLelmiszerek Kockázatnövelő Hatásaunclassified